+0  
 
0
434
2
avatar

(3x+3)-5=2(-2x+1)

 Nov 29, 2014

Best Answer 

 #1
avatar+20981 
+8

(3x+3) - 5  =  2(-2x + 1)

3x + 3 - 5  =  -4x + 2                        (Distribute the 2)

    3x - 2  =  -4x + 2                          (Simplify)

    7x - 2  =  2                                    (Add 4x to both sides)

        7x  =  4                                     (Add 2 to both sides)

         x  =  4/7                                  (Divide by 7)

 Nov 30, 2014
 #1
avatar+20981 
+8
Best Answer

(3x+3) - 5  =  2(-2x + 1)

3x + 3 - 5  =  -4x + 2                        (Distribute the 2)

    3x - 2  =  -4x + 2                          (Simplify)

    7x - 2  =  2                                    (Add 4x to both sides)

        7x  =  4                                     (Add 2 to both sides)

         x  =  4/7                                  (Divide by 7)

geno3141 Nov 30, 2014
 #2
avatar+285 
+3

yepp geno is right its 

3x + 3 - 5  =  -4x + 2                        

    3x - 2  =  -4x + 2                        

    7x - 2  =  2                                    

        7x  =  4                                   

         x  =  4/7          

 Nov 30, 2014

19 Online Users

avatar